Expression of the transcription factor Hes3 in the mouse and human ocular surface, and in pterygium. (August 2014) - Economopoulou, Matina; Masjkur, Jimmy; Raiskup, Frederik; Ebermann, Doreen; Saha, Sarama; Karl, Mike O.; Funk, Richard; Jaszai, Jozsef; Chavakis, Triantafyllos; Ehrhart-Bornstein, Monika; Pillunat, Lutz E.; Kunz-Schughart, Leoni; et al.
Abstract Purpose: In this work we examined the presence of the neural stem cell biomarker Hairy and Enhancer of Split 3 (Hes3) in the anterior eye segment and in the aberrant growth condition of the conjunctiva pterygium. Further, we studied the response of Hes3 to irradiation. Materials and methods: Adult mouse and human corneoscleral junction and conjunctiva, as well as human pterygium were prepared for immunohistochemical detection of Hes3 and other markers. Total body irradiation was used to study the changes in the pattern of Hes3 expression. Results: The adult rodent and human eye as well as pterygium, contain a population of cells expressing Hes3. In the human eye, Hes3-expressing (Hes3+) cells are found predominantly in the subconjunctival space spanning over the limbus where they physically associate with blood vessels. The cytoarchitecture of Hes3 + cells is similar to those previously observed in the adult central nervous system. Furthermore, irradiation reduces the number of Hes3 + cells in the subconjunctival space. In contrast, irradiation strongly promotes the nuclear localization of Hes3 in the ciliary body epithelium. Conclusions: Our results suggest that a recently identified signal transduction pathway that regulates neural stem cells and glioblastoma cancer stem cells also operates in the ocular surface, ciliary body, and in pterygium.